Sheet Metal 2011 - Duflou, Joost R.; Merklein, Marion; Micari, Fabrizio; Shirvani, Bez; et al. (Trans Tech Publications, 2011)
This work contains the proceedings of the 14th International Conference on Sheet Metal, held in Leuven, Belgium, from the 18th to the 20th April, 2011. Volume is indexed by Thomson Reuters CPCI-S (WoS). The objective of the International Conferences on Sheet Metal is to provide a forum where researchers, academics and industrialists can discuss and promote both the early dissemination of research results, and technology-transfer in sheet-metal processing. The conference provides an opportunity for those working on experimental research, as well as those involved in analytical and numerical modeling, to present their work. The contents therefore provide an unequalled overview of the fiel